Physical-chemical and sensory characteristics of cookies formulated with acerola (Malpighia emarginata D.C.) residues flour - Aquino, Ana Carolina Moura de Sena (2010)
Acerola pulp processed residues flour was used as a mixture material for cookies. The effect of the addition ofthis flour was evaluated in the cookies composition and acceptability. Formulations containing 0% (standard),10% (Type I) and 20% (Type II) of acerola residues flour were prepared partially replacing the wheat flour.The residue flour, consisting of peels and seeds, showed 8.60% humidity, 8.88% protein, 0.52% lipids, 3.03%ash, 24.33% of reducing sugars into glucose, 8.09 μg.g-1 of total carotenoids, 47.5°Brix, and 9549.61 mg ofascorbic acid.100g-1. The cookies prepared with acerola residue flour formulations were not well scored onthe global impression of them, being 5.34 (Type I) and 4.14 (Type II) when compared with the standardone (6.62). Improvements as adjusting the moisture contents have to be carried out for increasing cookiesacceptance. Neither total carotenoids nor ascorbic acid were detected in the standard cookies, however inType I cookies these substances rates were of 1.51 μg.g-1 and 2172.60 mg.100g-1, respectively. Acerola residueflour showed a distinct advantage owing to its high ascorbic acid contents, being an useful alternative forpartially replacing the wheat flour to improve the nutritional value of prepared cookies.